The criminal charges of legal persons against the phenomenon of organized crime - Luggren, Rosana Elizabeth (IUS ET VERITAS, 2016)
Facing the phenomenon of organized crime, the criminal justice system for legal persons is confronted with the need to adapt the theoretical structures in order to provide an answer to the challenges rising from the high degree complexity and volatility, common qualities of the contemporary societies. t he modern legislations claim different solutions, such as the vicarious liability “act like someone else” or “be in someone else’s place”, which allows transferring the responsibility or guilt of a person. t his, among others, is recognized as a dual justice system. It is believed that a specific justice system for legal persons should be reached and, taking into account its peculiarities, make it coexist with the proper system for physical persons.